2022
DOI: 10.3389/fendo.2022.895939
|View full text |Cite
|
Sign up to set email alerts
|

The role of endometrial thickness in predicting ectopic pregnancy after in vitro fertilization and the establishment of a prediction model

Abstract: ObjectiveTo explore the risk factors of ectopic pregnancy after in vitro fertilization.MethodsThis retrospective cohort study was conducted at the Reproductive Medical Center of the Third Affiliated Hospital of Zhengzhou University from January 2016 to April 2020. Univariate and multivariate analysis were used to analyze the related factors affecting the occurrence of ectopic pregnancy (EP) and to construct a nomographic prediction model for the incidence of ectopic pregnancy.ResultsA total of 12,766 cycles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Following this, mature oocytes (MII) were subjected to fertilization via intracytoplasmic sperm injection (ICSI). Embryos were cultured from pronuclear stage to cleavage stage in G1™ Plus (Vitrolife) after fertilization and then from cleavage stage to blastocyst stage in G-2™ Plus (Vitrolife) [ 25 ]. Embryo quality was evaluated based on previous literature [ 26 ], and day 3 embryos with a score of grade III or higher were designated as D3 available embryos in our institution.…”
Section: Methodsmentioning
confidence: 99%
“…Following this, mature oocytes (MII) were subjected to fertilization via intracytoplasmic sperm injection (ICSI). Embryos were cultured from pronuclear stage to cleavage stage in G1™ Plus (Vitrolife) after fertilization and then from cleavage stage to blastocyst stage in G-2™ Plus (Vitrolife) [ 25 ]. Embryo quality was evaluated based on previous literature [ 26 ], and day 3 embryos with a score of grade III or higher were designated as D3 available embryos in our institution.…”
Section: Methodsmentioning
confidence: 99%
“…The conventional gonadotrophin-releasing hormone agonist (GnRH-a) (Diphereline, lpsen, France) long protocols of our center were used for ovulation stimulation (8), and eggs were collected 36-38 h after human chorionic gonadotropin (hCG) injection.…”
Section: Controlled Ovarian Hyperstimulationmentioning
confidence: 99%
“…Despite significant improvements in the incidence of EP with FET compared with fresh transfer (1%-2% [1,2] and 2%-8% [1,3] , respectively), methods to predict the incidence of EP in FET are not fully understood. Some studies have found that endometrial thickness (EMT) is an independent risk factor for EP in IVF/FET [4][5][6][7][8][9] ; however, studies have proposed different threshold levels of EMT, ranging from 7.6 to 12.0 mm. Thus, it may be important to identify the risk factors for EP and predict the endometrial characteristics associated with EP after ART.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that endometrial thickness (EMT) is an independent risk factor for EP in IVF/FET [4–9] ; however, studies have proposed different threshold levels of EMT, ranging from 7.6 to 12.0 mm. Thus, it may be important to identify the risk factors for EP and predict the endometrial characteristics associated with EP after ART.…”
Section: Introductionmentioning
confidence: 99%